The effect of spatial organization of cafes on users' perceptual evaluations - Yildirim, Kemal; Muezzinoglu, Mensure Kubra; Kahraman, Necmi (Gazi Univ, Fac Engineering Architecture, 2024)
Purpose: Previous research show that different spatial organization in caf & eacute;s can affect users' perceptual evaluations. In this research, participants' perceptual evaluations of the physical environmental factors of caf & eacute;s withregular, irregular and very irregular space organization were analyzed (Figure A). Theory and Methods: To test the hypotheses of this research, the participants were asked to evaluate caf & eacute; spaces through a developed survey form. Research data was obtained from 192 participants with the help of a detailed survey. Results: According to the analysis of the survey data, it was determined that the physical environmental factors ofthe regular caf & eacute; were perceived more positively for appeal, planning and freedom factors than the irregularand very irregular caf & eacute;s. Accordingly, it seems that caf & eacute;s are perceived more negatively depending on theincrease in disorder. On the other hand, it was determined that the age difference of the participants wasnot statistically effective in the perception of the environmental factors of caf & eacute;s with different furniture arrangements, but the differences in the participants' profession, gender and education level were effective. Conclusion: Therefore, it was determined that those who received design education, women and those with highereducation had a more negative approach in their perceptual evaluations. The results of this research clearlyshowed that the different furniture arrangements often encountered in caf & eacute; cause significant effects on users'perceptual evaluations.
Kafelerde mekân organizasyonunun kullanıcıların algısal değerlendirmeleri üzerindeki etkisi
Keywords: Caf & eacute;; Spatial organization; Interior design; Furniture organization